2018
DOI: 10.3389/fpsyg.2018.01445
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Household Size on Lexical Typicality: An Early Link Between Language and Social Cognition?

Abstract: To communicate successfully, speakers need to use words that are understood by their listeners; they thus need to understand that others have vocabularies different than their own. A key question is whether this social cognition skill is already present in infancy, and whether it can have an impact on early language production. Analysis of the vocabularies of 550 Mexican children revealed that, at 24 months of age, but not at 18 nor at 30 months of age, those who were raised in households with larger numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…For rural children, more siblings also correlated to a smaller number of adult words overheard in the household, as well as a smaller number of adult–child conversations, while for peri‐urban children, more siblings correlated to fewer child vocalizations. These findings reflect previous research that has shown that children with more siblings have lower levels of both word production and comprehension (Mayor et al., 2018). Finally, dividing households according to who acted as the primary caregiver, we found that households in which the grandmother was the primary caregiver had significantly higher AWC and CTC (but not CDI) than those in which the mother was the primary caregiver (Table S5).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For rural children, more siblings also correlated to a smaller number of adult words overheard in the household, as well as a smaller number of adult–child conversations, while for peri‐urban children, more siblings correlated to fewer child vocalizations. These findings reflect previous research that has shown that children with more siblings have lower levels of both word production and comprehension (Mayor et al., 2018). Finally, dividing households according to who acted as the primary caregiver, we found that households in which the grandmother was the primary caregiver had significantly higher AWC and CTC (but not CDI) than those in which the mother was the primary caregiver (Table S5).…”
Section: Discussionsupporting
confidence: 91%
“…Household wealth (asset index) has been shown to be associated with ECD as well (Gilkerson et al., 2018; Yue et al., 2017). Finally, the number of adults and siblings in the household was collected because previous studies suggest that household size is an influential factor in the HLE and language development (Mayor et al., 2018; McCartney, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…To measure the value of household assets, we created a family asset index for all households using polychoric principal components analysis based on whether the family owned or had access to running water, a toilet, a water heater, a washing machine, a computer, Internet access, a refrigerator, air conditioning, a motorcycle, and a car/truck [ 43 ]. Additionally, we collected data on the number of siblings and adults in the household, as it has been suggested that household size is an influential factor in the home language environment and language development [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Identity of the primary caregiver was collected because previous research has shown that about one-third of primary caregivers of young children in rural China are actually grandmothers, not mothers, and that caregiver type affects early childhood development outcomes [9]. Finally, the numbers of adults and siblings in the household were collected as it has been suggested that household size is an influential factor in the home language environment and language development [69,70].…”
Section: Demographic Informationmentioning
confidence: 99%